2021
DOI: 10.1371/journal.pone.0251584
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between neonatal hyperbilirubinemia and vitamin D levels: A meta-analysis

Abstract: Objective Hyperbilirubinemia is a common disease in the neonatal period, and hyperbilirubinemia may cause brain damage. Therefore, prevention and diagnosis and management of hyperbilirubinemia is very important, and vitamin D may affect bilirubin levels. To evaluate the relationship between neonatal hyperbilirubinemia and vitamin D levels. Method The China National Knowledge Infrastructure, VIP, Wanfang, Chinese Biology Medicine Disc, PubMed, Web of Science, Cochrane Library, and Embase databases as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
2
12
0
1
Order By: Relevance
“…This was consistent with the findings of Wijaya et al (2018), which found breastfeeding to be associated with the incidence of hyperbilirubinemia with a p-value of 0.001. 8 The similar results were found by Huang et al (2021) with a p-value of 0.033. 15 Neonates with inadequate breastmilk intake during breastfeeding had not enough milk reach their intestines to process bilirubin elimination from the body.…”
Section: Original Articlesupporting
confidence: 83%
See 1 more Smart Citation
“…This was consistent with the findings of Wijaya et al (2018), which found breastfeeding to be associated with the incidence of hyperbilirubinemia with a p-value of 0.001. 8 The similar results were found by Huang et al (2021) with a p-value of 0.033. 15 Neonates with inadequate breastmilk intake during breastfeeding had not enough milk reach their intestines to process bilirubin elimination from the body.…”
Section: Original Articlesupporting
confidence: 83%
“…8 The similar results were found by Huang et al (2021) with a p-value of 0.033. 15 Neonates with inadequate breastmilk intake during breastfeeding had not enough milk reach their intestines to process bilirubin elimination from the body. This occurs in preterm babies whose mothers do not produce enough breastmilk.…”
Section: Original Articlesupporting
confidence: 83%
“…Further studies are also needed to address whether bilirubin-dependent FGF23 suppression affects mineral metabolism. In fact, serum vitamin D levels are lower in neonates with hyperbilirubinemia [66]. Additionally, dietary calcium phosphate ameliorates hyperbilirubinemia in rats [67].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, neonates with NH had a higher rate of vitamin D deficiency compared with the controls, but there was no significant difference after adjusting for potential confounding variables. The relationship between vitamin D and NH is not well studied so far, the mechanism remains to be discovered, and the possible explanations for their relationship are as follows [ 10 , 26 ]. Firstly, vitamin D can reduce erythropoietin levels in the blood, which can decrease the lysis of red blood cells and bilirubin production; Secondly, vitamin D can slow down oxidative stress, cell and tissue damage [ 27 ], which may help prevent the accumulation of bilirubin levels induced by red blood cell oxidative damage; Thirdly, the liver is the important organ for the metabolism of both bilirubin and vitamin D, so, their metabolic processes may have potential interaction.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study from Iran revealed a lack of a correlation between vitamin D levels and NH[ 8 ]. A recent meta-analysis showed that vitamin D level of the NH group was significantly lower than that in the healthy control group, and its subgroup analysis based on the bilirubin level of the study indicated that vitamin D levels might cause differences in the degree of NH[ 10 ]. Therefore, we speculated that low vitamin D level is a risk factor for NH and may also be linked to severe NH.…”
Section: Discussionmentioning
confidence: 99%